Battery and battery production method

By using an electrode material layer and an electrolyte sheet without adhesive in a solid-state lithium battery, and increasing the material density through isostatic pressure treatment, the problem of low conductivity in the prior art is solved, and the battery current transmission efficiency and capacity energy density are improved.

CN119627182APending Publication Date: 2025-03-14EVE ENERGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411833333.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The electrode material layer and electrolyte sheet of the conventional solid-state lithium battery contain adhesives, which reduces the conductivity and thus reduces the charge and discharge efficiency of the battery.

Method used

An electrode material layer and an electrolyte sheet without adhesive are used, and the material components include electrode active material, conductive agent and solid electrolyte, and the high density and uniformity of the material are ensured through isostatic pressure treatment.

Benefits of technology

The conductivity of the electrode sheet is improved, the current transmission efficiency in the battery is enhanced, the capacity and energy density of the battery are improved, and the density reduction problem caused by adhesives is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627182A_ABST
    Figure CN119627182A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and discloses a battery and a battery production method.The battery cell of the battery comprises an electrode plate, the electrode plate comprises an electrode material layer, and the material components of the electrode material layer comprise an electrode active material and a conductive agent and do not comprise an adhesive, so that the conductivity of the electrode material layer is almost not affected; the conductivity of the electrode material layer can be improved, so that the transmission efficiency of current in the battery is improved. In the battery production method, the material required for producing the electrode material layer is put into the mold, and the material in the mold is subjected to isostatic pressing treatment, so that the material in the mold is compacted tightly under the action of pressure, and the isostatic pressing treatment can improve the density uniformity of the electrode material layer; the problems of non-uniform stress distribution, non-uniform temperature distribution and the like on the electrode plate can be avoided, and then the electrode material layer is prevented from falling off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a battery and a battery production method. Background Art

[0002] The battery cell of a solid-state lithium battery includes a positive electrode sheet, a negative electrode sheet and an electrolyte sheet, and the electrolyte sheet is arranged between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet and the negative electrode sheet are collectively referred to as electrode sheets, and the electrode sheet includes a current collector and an electrode material layer arranged on the current collector. For example, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer arranged on the positive electrode current collector, and the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer arranged on the negative electrode current collector.

[0003] In the prior art, the material components of the electrode material layer contain adhesives. When producing the electrode material layer, the material used for the electrode material layer is mixed with the adhesive to form a slurry, and the slurry is coated on the current collector and dried to form the electrode material layer, or the slurry is extruded into a film, and the film is rolled and compounded with the electrolyte sheet and then cut to form a positive electrode sheet. The material components of the electrolyte sheet also contain adhesives. When producing the electrolyte sheet, the solid electrolyte material and the adhesive are mixed into a slurry, and the slurry is extruded into a film, and the film is cut to form a single electrolyte sheet.

[0004] Although the presence of the adhesive makes the materials in the electrode material layer and the electrolyte sheet firmly bonded together, it will reduce the conductivity of the electrode material layer and the electrolyte sheet, resulting in reduced current transmission efficiency in the battery and reduced battery charge and discharge efficiency. Summary of the invention

[0005] The first object of the present application is to provide a battery, which can improve the conductivity of the electrode material layer of the electrode sheet of the battery, thereby improving the current transmission efficiency in the battery including the electrode sheet.

[0006] To achieve the above objectives, this application adopts the following technical solutions:

[0007] A battery is provided, comprising a battery cell, the battery cell comprising an electrode sheet, the electrode sheet (10) comprising an electrode material layer, the material components of the electrode material layer do not include an adhesive, and the material components of the electrode material layer include an electrode active material and a conductive agent.

[0008] As some embodiments of the battery provided in the present application, the material components of the electrode material layer also include a solid electrolyte.

[0009] As some embodiments of the battery provided in the present application, the mass proportion of the electrode active material in the electrode material layer is greater than or equal to 65% and less than or equal to 89%, and the mass proportion of the electrode active material is the percentage of the mass of the electrode active material in the electrode material layer to the total mass of the electrode material layer;

[0010] And / or, the mass proportion of the solid electrolyte in the electrode material layer is greater than or equal to 5% and less than or equal to 35%, and the mass proportion of the solid electrolyte is the percentage of the mass of the solid electrolyte in the electrode material layer to the total mass of the electrode material layer;

[0011] And / or, the mass proportion of the conductive agent in the electrode material layer is greater than or equal to 0.5% and less than or equal to 5%, and the mass proportion of the conductive agent is the percentage of the mass of the conductive agent in the electrode material layer to the total mass of the electrode material layer.

[0012] As some embodiments of the battery provided in the present application, the ratio of the actual density of the electrode material layer to the theoretical density of the electrode material layer is greater than or equal to 95%.

[0013] As some embodiments of the battery provided in the present application, the electrode sheet further includes a current collector, and the electrode material layer is laminated on at least one side of the current collector.

[0014] As some embodiments of the battery provided in the present application, the electrode sheet further includes a conductive adhesive layer, and the electrode material layer and the current collector are adhesively connected via the conductive adhesive layer.

[0015] As some embodiments of the battery provided in the present application, the electrode sheet further includes an electrolyte sheet, and the material components of the electrolyte sheet include a solid electrolyte and do not include a binder.

[0016] As some embodiments of the battery provided in the present application, the ratio of the actual density of the electrolyte sheet to the theoretical density of the electrolyte sheet is greater than or equal to 95%.

[0017] The second object of the present application is to provide a battery production method for producing the battery as described above, which can ensure that the density of the electrode material layer meets the production requirements and improve the density uniformity of various parts of the electrode material layer.

[0018] To achieve the above objectives, this application adopts the following technical solutions:

[0019] A battery production method is provided for producing the battery as described above, wherein the battery production method includes a method for producing an electrode sheet, and the method for producing an electrode sheet includes:

[0020] placing materials required for manufacturing the electrode material layer into a mold;

[0021] The material in the mold is subjected to isostatic pressing so that the ratio of the actual density of the material in the mold to the theoretical density of the material in the mold is greater than or equal to 95%.

[0022] As some embodiments of the battery production method provided in the present application, the thickness of the electrode material layer to be produced is a first preset thickness;

[0023] After isostatic pressing the material in the mold, the material in the mold is formed into an electrode material layer having a thickness satisfying a first preset thickness; or,

[0024] After the material in the mold is subjected to isostatic pressing, the material in the mold is formed into an electrode block, and the thickness of the electrode block is greater than a first preset thickness; the production method of the electrode sheet also includes: cutting the electrode block along a first preset direction to divide the electrode block into a plurality of electrode material layers, and the first preset direction is perpendicular to the thickness direction of the electrode material layer.

[0025] As some embodiments of the battery production method provided in the present application, the battery production method also includes a method for producing an electrolyte sheet, and the method for producing an electrolyte sheet includes:

[0026] placing materials required for manufacturing the electrolyte sheet into a mold;

[0027] The material in the mold is subjected to isostatic pressing so that the ratio of the actual density of the material in the mold to the theoretical density of the material in the mold is greater than or equal to 95%.

[0028] As some embodiments of the battery production method provided by the present application, the thickness of the electrolyte sheet to be produced is a second preset thickness;

[0029] After isostatic pressing the material in the mold, the material in the mold is formed into an electrolyte sheet having a thickness satisfying a second preset thickness; or,

[0030] After isostatic pressing is performed on the material in the mold, the material in the mold is formed into an electrolyte block, and the thickness of the electrolyte block is greater than the second preset thickness; the production method of the electrolyte sheet also includes: cutting the electrolyte block along a second preset direction to divide the electrolyte block into a plurality of electrolyte sheets, and the second preset direction is perpendicular to the thickness direction of the electrolyte sheet.

[0031] Beneficial effects of this application:

[0032] In the battery provided by the present application, since the material components of the electrode material layer of the electrode sheet do not contain an adhesive, there is almost no effect on the electrical conductivity of the electrode material layer. Compared with the electrode material layer with the addition of an adhesive, the electrical conductivity of the electrode material layer of the electrode sheet of the present application can be improved, thereby improving the current transmission efficiency in the battery.

[0033] In the battery production method provided by the present application, when producing the electrode material layer of the electrode sheet, the material required for producing the electrode material layer is placed in a mold, and the material in the mold is subjected to isostatic pressing so that the material in the mold is compacted tightly under pressure, and no adhesive is added to the material required for producing the electrode material layer, so as to ensure that the ratio of the actual density of the material in the mold to the theoretical density of the material in the mold can reach greater than or equal to 95%, thereby producing an electrode material layer with a high density, which helps to improve the capacity and energy density of the battery. Moreover, isostatic pressing can improve the density uniformity of the electrode material layer, and when the battery is working, it can avoid problems such as uneven stress distribution and uneven temperature distribution on the electrode sheet, thereby preventing the electrode material layer from falling off. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0035] Figure 1 It is a schematic diagram of the structure of the electrode sheet provided in a specific embodiment of the present application;

[0036] Figure 2 It is a structural schematic diagram of a positive electrode sheet provided in a specific embodiment of the present application;

[0037] Figure 3 It is a schematic diagram of the structure of another positive electrode sheet provided in a specific embodiment of the present application;

[0038] Figure 4 It is a schematic diagram of the structure of a negative electrode sheet provided in a specific embodiment of the present application;

[0039] Figure 5 It is a schematic diagram of the structure of another negative electrode sheet provided in a specific embodiment of the present application;

[0040] Figure 6 It is a structural schematic diagram of an electrode block provided in a specific embodiment of the present application;

[0041] Figure 7 is a schematic diagram of the structure of the electrolyte block provided in a specific embodiment of the present application;

[0042] Figure 8 It is a structural schematic diagram of a battery cell provided in a specific embodiment of the present application;

[0043] Fig. 9 It is a structural schematic diagram of another battery cell provided in a specific embodiment of the present application;

[0044] Fig.10 It is a schematic diagram of the structure of a battery provided in a specific embodiment of the present application.

[0045] In the figure:

[0046] 10. electrode sheet; 11. electrode material layer; 12. current collector; 13. conductive adhesive layer; 14. insulating adhesive layer; 20. electrode block; 30. electrolyte block;

[0047] 100, battery cell; 200, packaging structure; 300, connecting piece; 400, heat conducting layer; 500, positive electrode ear of battery; 600, negative electrode ear of battery;

[0048] 110, positive electrode sheet; 120, negative electrode sheet; 130, electrolyte sheet;

[0049] 111, positive electrode current collector; 112, positive electrode material layer; 1110, positive electrode ear;

[0050] 121. negative electrode current collector; 122. negative electrode material layer; 1210. negative electrode tab. DETAILED DESCRIPTION

[0051] The present application will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only the parts related to the present application, rather than all structures, are shown in the accompanying drawings.

[0052] In the description of this application, unless otherwise clearly specified and limited, the terms "connected", "connected", and "fixed" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0053] In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.

[0054] In the description of this embodiment, the terms "upper", "lower", "left", "right" and other directions or positional relationships are based on the directions or positional relationships shown in the drawings, and are only for the convenience of description and simplified operation, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation of the present application. In addition, the terms "first" and "second" are only used to distinguish in the description and have no special meaning.

[0055] In this embodiment, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this application generally indicates that the associated objects before and after are in an "or" relationship.

[0056] In the embodiments of the present application, the same reference numerals represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.

[0057] The present application embodiment provides a battery, the battery comprising a battery cell, the battery cell comprising an electrode sheet. Figure 1 As shown, it is a schematic diagram of the electrode sheet 10 provided in an embodiment of the present application, which can improve the conductivity of the electrode sheet 10, thereby improving the current transmission efficiency in the battery including the electrode sheet 10, and can also improve the capacity and energy density of the battery.

[0058] like Figure 1 As shown, the electrode sheet 10 includes an electrode material layer 11. The material components of the electrode material layer 11 include an electrode active material and a conductive agent, and the material components of the electrode material layer 11 do not include a binder.

[0059] In the electrode sheet 10 provided in the embodiment of the present application, since the material components of the electrode material layer 11 of the electrode sheet 10 do not include an adhesive, there is almost no effect on the electrical conductivity of the electrode material layer 11. Compared with the electrode material layer to which an adhesive is added, the electrical conductivity of the electrode material layer 11 of the electrode sheet 10 of the present application can be improved, thereby improving the transmission efficiency of the current in the battery and improving the charging and discharging efficiency of the battery.

[0060] In the embodiment of the present application, the ratio of the actual density of the electrode material layer 11 to the theoretical density of the electrode material layer 11 (ie, the density) is greater than or equal to 95%.

[0061] In the prior art, since the electrode material layer 11 contains a material component, which is an adhesive, and the adhesive is an elastic polymer, it is difficult to achieve a high density when the electrode material layer 11 is compacted. Specifically, in the existing electrode sheet, the ratio of the actual density of the electrode material layer to the theoretical density of the electrode material layer is approximately 90%. Moreover, after the electrode material layer has been left to stand for a period of time, due to the strong elasticity of the adhesive, there is a problem of rebound of the electrode material layer, which causes the density of the electrode material layer of the electrode sheet to further drop to about 85%. However, since the electrode material layer 11 provided in the embodiment of the present application does not contain a material component, which can eliminate the influence of the adhesive on the density, after the electrode material layer 11 is compacted, the ratio of the actual density of the electrode material layer 11 to the theoretical density of the electrode material layer 11 can be greater than or equal to 95%, that is, the electrode material layer 11 has a higher density, thereby improving the capacity and energy density of the battery. Furthermore, since the electrode material layer 11 does not contain an adhesive, the problem of the electrode material layer 11 rebounding and causing a decrease in density will not occur, and the density of the electrode material layer 11 can be stably maintained at a level greater than or equal to 95%.

[0062] The electrode material layer 11 of the electrode sheet 10 provided in the embodiment of the present application, when the material components do not include an adhesive, can have a ratio of actual density to the theoretical density of the electrode material layer 11 that is greater than or equal to 95%, thereby allowing the electrode sheet 10 to have a higher density while improving electrical conductivity, which is beneficial to improving the capacity and energy density of the battery.

[0063] In the embodiment of the present application, the material components of the electrode material layer 11 include electrode active materials, solid electrolytes and conductive agents, but do not include adhesives. The electrode active material is the core part of the battery for electrochemical reactions, and realizes the storage and release of electrical energy through redox reactions. The solid electrolyte in the electrode material layer 11 plays the role of conducting charged ions (such as lithium ions), which has an important influence on the efficiency and stability of ion transmission. Since the conductivity of the electrode active material itself may be limited, adding a conductive agent to the electrode material layer 11 helps to improve the conductivity of the electrode sheet 10, thereby improving the rate performance and charge and discharge efficiency of the battery.

[0064] In some embodiments, the mass proportion of the electrode active material in the electrode material layer 11 is greater than or equal to 65% and less than or equal to 89%, and the mass proportion of the electrode active material is the percentage of the mass of the electrode active material in the electrode material layer 11 to the total mass of the electrode material layer 11. In the electrode material layer 11 provided in the embodiment of the present application, by limiting the mass proportion of the electrode active material to be greater than or equal to 65% and less than or equal to 89%, the mass proportion of the electrode active material can be neither too large nor too small. If the mass proportion of the electrode active material is too large, the mass proportion of the solid electrolyte and the conductive agent in the electrode material layer 11 will be small, thereby reducing the transmission efficiency and transmission stability of the ions in the electrode material layer 11, deteriorating the conductivity of the electrode sheet 10, and causing waste of the electrode active material. If the mass proportion of the electrode active material is too small, the capacity and energy density of the battery will be reduced.

[0065] Exemplarily, the mass percentage of the electrode active material in the electrode material layer 11 is 65%, 68%, 69.2%, 70%, 74%, 75%, 78.6%, 85%, 88.8%, 89%, etc., but is not limited to the data listed above.

[0066] In some embodiments, the mass proportion of the solid electrolyte in the electrode material layer 11 is greater than or equal to 5% and less than or equal to 35%, and the mass proportion of the solid electrolyte is the percentage of the mass of the solid electrolyte in the electrode material layer 11 to the total mass of the electrode material layer 11. In the electrode material layer 11 provided in the embodiment of the present application, by limiting the mass proportion of the solid electrolyte to be greater than or equal to 5% and less than or equal to 35%, the mass proportion of the solid electrolyte can be neither too large nor too small. If the mass proportion of the solid electrolyte is too large, the mass proportion of the electrode active material in the electrode material layer 11 will be small, resulting in a lower capacity and energy density of the battery, and will cause a waste of solid electrolyte materials. If the mass proportion of the solid electrolyte is too small, the transmission efficiency and transmission stability of ions in the electrode material layer 11 will be reduced.

[0067] Exemplarily, the mass percentage of the solid electrolyte in the electrode material layer 11 is 5%, 7.5%, 8%, 9.2%, 11%, 17%, 19.5%, 20%, 22%, 25%, 26.3%, 28%, 30%, 31.4%, 32.5%, 35%, etc., but is not limited to the data listed above.

[0068] In some embodiments, the mass proportion of the conductive agent in the electrode material layer 11 is greater than or equal to 0.5% and less than or equal to 5%, and the mass proportion of the conductive agent is the percentage of the mass of the conductive agent in the electrode material layer 11 to the total mass of the electrode material layer 11. In the electrode material layer 11 provided in the embodiment of the present application, by limiting the mass proportion of the conductive agent to be greater than or equal to 0.5% and less than or equal to 5%, the mass proportion of the conductive agent can be neither too large nor too small. If the mass proportion of the conductive agent is too large, the mass proportion of the electrode active material and the mass proportion of the solid electrolyte in the electrode material layer 11 will be small, resulting in a low capacity and energy density of the battery, reduced ion transmission efficiency and transmission stability, resulting in the battery being unable to fully exert its theoretical capacity, reducing the actual available power, reducing the battery charging efficiency, and accelerating the battery aging. If the mass proportion of the conductive agent is too small, the battery's conductivity will decrease, the charge and discharge efficiency will decrease, the rate performance will deteriorate, and the efficiency of the electrode active material will not be fully exerted, affecting the battery's energy density and capacity.

[0069] Exemplarily, the mass proportion of the conductive agent in the electrode material layer 11 is 0.5%, 0.7%, 0.75%, 1%, 1.9%, 2%, 2.2%, 2.5%, 3%, 3.4%, 3.9%, 4%, 4.3%, 4.4%, 4.5%, 4.8%, 5%, etc., but is not limited to the data listed above.

[0070] In the electrode sheet 10 provided in this embodiment, the mass proportion of each material component in its electrode material layer 11 is: the mass proportion of the electrode active material is greater than or equal to 65% and less than or equal to 89%, the mass proportion of the solid electrolyte is greater than or equal to 5% and less than or equal to 35%, and the mass proportion of the conductive agent is greater than or equal to 0.5% and less than or equal to 5%.

[0071] See also Figure 1 The electrode sheet 10 further includes a current collector 12, and an electrode material layer 11 is stacked on at least one side of the current collector 12. The current collector 12, as a carrier of the electrode material layer 11, can provide physical support for the electrode material layer 11 and enable the current to flow smoothly in the battery. The current collector 12 is exemplarily a copper foil or an aluminum foil. The electrode material layer 11 can be stacked on one side of the current collector 12, or a layer of electrode material layer 11 can be stacked on both sides of the current collector 12.

[0072] See also Figure 1The electrode sheet 10 further includes a conductive adhesive layer 13, and the electrode material layer 11 and the current collector 12 are bonded and connected by the conductive adhesive layer 13. On the one hand, by providing the conductive adhesive layer 13, the electrode material layer 11 and the current collector 12 can be firmly bonded together, so as to prevent the electrode material layer 11 from falling off on the current collector 12, thereby improving the stability and reliability of the electrode sheet 10; on the other hand, the provision of the conductive adhesive layer 13 can make the electrode material layer 11 and the current collector 12 fully conductively contacted, ensure that there is a good electron transmission channel between the electrode material layer 11 and the current collector 12, reduce the contact resistance, and improve the conductive performance of the entire electrode sheet 10.

[0073] like Figure 2 and Figure 3 As shown, the electrode sheet 10 provided in the embodiment of the present application is a positive electrode sheet 110, wherein the positive electrode sheet 110 includes a positive electrode current collector 111 and a positive electrode material layer 112 stacked on the positive electrode current collector 111. That is, the electrode material layer 11 of the above-mentioned electrode sheet 10 is the positive electrode material layer 112, and the current collector 12 is the positive electrode current collector 111. A conductive adhesive layer 13 is provided between the positive electrode current collector 111 and the positive electrode material layer 112, which is used to bond the positive electrode current collector 111 and the positive electrode material layer 112 together and ensure that the positive electrode current collector 111 and the positive electrode material layer 112 are in good conductive contact.

[0074] In some embodiments, such as Figure 2 As shown, a positive electrode material layer 112 is stacked on one side of the positive electrode current collector 111, and the positive electrode current collector 111 and the positive electrode material layer 112 are bonded by a conductive adhesive layer 13. At this time, a negative electrode sheet 120 can be stacked on the side of the positive electrode material layer 112 facing away from the positive electrode current collector 111.

[0075] In some embodiments, Figure 3 As shown, positive electrode material layers 112 are stacked on both sides of the positive electrode current collector 111, and the positive electrode current collector 111 and the positive electrode material layers 112 on both sides are bonded by conductive adhesive layers 13. At this time, negative electrode plates 120 can be stacked on the side of each positive electrode material layer 112 facing away from the positive electrode current collector 111.

[0076] For the positive electrode material layer 112, the electrode active material in its material components is a positive electrode active material. The optional range of positive electrode active materials is: NCM (high nickel ternary positive electrode material), NCA (nickel cobalt aluminum), lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium-rich positive electrode, sulfur positive electrode and its derivatives, preferably NCA and lithium cobalt oxide. Any one of the above materials or a combination of at least two of them can be used to produce the positive electrode material layer 112.

[0077] like Figure 4 and Figure 5As shown, the electrode sheet 10 provided in the embodiment of the present application is a negative electrode sheet 120, wherein the negative electrode sheet 120 includes a negative electrode current collector 121 and a negative electrode material layer 122 stacked on the negative electrode current collector 121. That is, the electrode material layer 11 of the above-mentioned electrode sheet 10 is the negative electrode material layer 122, and the current collector 12 is the negative electrode current collector 121. A conductive adhesive layer 13 is provided between the negative electrode current collector 121 and the negative electrode material layer 122, which is used to bond the negative electrode current collector 121 and the negative electrode material layer 122 together, and ensure that the negative electrode current collector 121 and the negative electrode material layer 122 have good conductive contact.

[0078] In some embodiments, such as Figure 4 As shown, a negative electrode material layer 122 is stacked on one side of the negative electrode current collector 121, and the negative electrode current collector 121 and the negative electrode material layer 122 are bonded by a conductive adhesive layer 13. At this time, a positive electrode sheet 110 can be stacked on the side of the negative electrode material layer 122 facing away from the negative electrode current collector 121.

[0079] In some embodiments, Figure 5 As shown, negative electrode material layers 122 are stacked on both sides of the negative electrode current collector 121, and the negative electrode current collector 121 and the negative electrode material layers 122 on both sides are bonded by conductive adhesive layers 13. At this time, positive electrode sheets 110 can be stacked on the side of each negative electrode material layer 122 facing away from the positive electrode current collector 111.

[0080] For the negative electrode material layer 122, the electrode active material in its material components is the negative electrode active material. The optional range of the negative electrode active material is: silicon oxygen negative electrode material, silicon carbon negative electrode material, tin carbon negative electrode material, lithium titanate, graphite, etc., among which silicon carbon negative electrode material and lithium titanate are preferred. Any one of the above materials or a combination of at least two of them can be selected to produce the negative electrode material layer 122.

[0081] For the positive electrode material layer 112 and the negative electrode material layer 122, the optional range of solid electrolytes in their material components includes sulfide electrolytes, halide electrolytes, oxide electrolytes, and polymer electrolytes. Sulfide electrolytes include LPSCl (lithium phosphorus sulfur chloride), LGPS (germanium phosphorus sulfur lithium ion solid electrolyte) and their derivatives; halide electrolytes include Li3YCl6, Li3InCl6 and their derivatives; oxide electrolytes include LLZO (lithium lanthanum zirconium oxide), LATP (lithium aluminum titanium phosphate), LLTO (lithium lanthanum titanate) and their derivatives. Any one of the above materials or a combination of at least two of them can be selected.

[0082] For the positive electrode material layer 112 and the negative electrode material layer 122 , the conductive agent in the material components thereof may be selected from the following ranges: conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes, etc. Any one of the above materials or a combination of at least two of them may be selected.

[0083] An embodiment of the present application also provides a battery production method, which includes an electrode sheet production method for producing an electrode sheet 10 as described above. The electrode sheet production method can ensure that the density of the electrode material layer 11 meets the production requirements and improve the density uniformity of each part of the electrode material layer 11.

[0084] The production method of the electrode sheet provided in the present application comprises:

[0085] S1, placing materials required for manufacturing the electrode material layer 11 into a mold;

[0086] S2. Perform isostatic pressing on the material in the mold so that the ratio of the actual density of the material in the mold to the theoretical density of the material in the mold is greater than or equal to 95%.

[0087] In the production method of the electrode sheet provided in the present application, the material required for producing the electrode material layer 11 is placed in a mold, and the material in the mold is subjected to isostatic pressing so that the material in the mold is compacted tightly under pressure. No adhesive is needed to be added to the material required for producing the electrode material layer 11. Only isostatic pressing can ensure that the ratio of the actual density of the material in the mold to the theoretical density of the material in the mold can reach greater than or equal to 95%, thereby producing an electrode material layer 11 with a high density, which helps to improve the capacity and energy density of the battery. Moreover, isostatic pressing can improve the density uniformity of the electrode material layer 11. When the battery is working, it can avoid problems such as uneven stress distribution and uneven temperature distribution on the electrode sheet 10, thereby preventing the electrode material layer 11 from falling off, and avoiding problems such as too fast decrease in battery capacity, increase in battery internal resistance, and severe heat generation.

[0088] The thickness of the electrode material layer 11 to be produced is set to a first preset thickness. After the material in the mold is subjected to isostatic pressing, the electrode material layer 11 can be directly formed or the electrode material layer 11 can be formed by cutting the material after the isostatic pressing.

[0089] Specifically, in some embodiments, after the material in the mold is subjected to isostatic pressing, the material in the mold is formed into a sheet-shaped electrode material layer 11 under pressure, and the thickness of the electrode material layer 11 meets the first preset thickness. That is, each isostatic pressing process forms a sheet of electrode material layer 11.

[0090] In other embodiments, after the material in the mold is subjected to isostatic pressing, the material in the mold is formed into Figure 6 The electrode block 20 shown in FIG. The thickness of the electrode block 20 is greater than the first preset thickness.

[0091] The production method of the electrode sheet further includes: after the electrode block 20 is formed, cutting the electrode block 20 along a first preset direction to divide the electrode block 20 into a plurality of electrode material layers 11, wherein the first preset direction is perpendicular to the thickness direction of the electrode material layer 11. Figure 6 , the electrode material layer 11 is parallel to the plane where the X direction and the Y direction are located (i.e., the XY plane), the thickness direction of the electrode material layer 11 is the Z direction, and the thickness direction of the electrode block 20 is also the Z direction. The X direction, the Y direction, and the Z direction are perpendicular to each other. The first preset direction is parallel to the plane where the X direction and the Y direction are located, and the electrode block 20 is cut multiple times along the first preset direction so that the electrode block 20 is divided into a plurality of layers of electrode material layers 11, and the thickness of each layer of the electrode material layer 11 meets the first preset thickness.

[0092] The solution of first isostatically pressing the material in the mold to form the electrode block 20 and then cutting the electrode block 20 along a first preset direction can improve the production efficiency of the electrode material layer 11, and facilitate the control of the thickness of the electrode material layer 11 to ensure the uniformity of the thickness of the electrode material layer 11.

[0093] When the electrode block 20 is cut to form the electrode material layer 11, burrs are formed at the edge of the electrode material layer 11. Since the electrode block 20 is cut along the first preset direction, the burrs formed at the edge of the electrode material layer 11 can extend along the first preset direction. That is, the point of the burr farthest from the electrode material layer 11 and the vertical line between the electrode material layer 11 are parallel to the XY plane.

[0094] The positive electrode material layer 112 and the negative electrode material layer 122 can be produced by the above-mentioned electrode sheet production method, and the burrs on the edge of the produced positive electrode material layer 112 extend along the first preset direction (i.e., parallel to the XY plane), and the burrs on the edge of the produced negative electrode material layer 122 extend along the first preset direction (i.e., parallel to the XY plane). Figure 8 In the battery cell 100 shown, the positive electrode sheet 110, the electrolyte sheet 130 and the negative electrode sheet 120 are stacked in sequence, and the positive electrode material layer 112 and the negative electrode material layer 122 are in contact with the electrolyte sheet 130. The positive electrode sheet 110, the electrolyte sheet 130 and the negative electrode sheet 120 are all parallel to the XY plane. Since the burrs on the edge of the positive electrode material layer 112 and the burrs on the edge of the negative electrode material layer 122 are all parallel to the XY plane, the burrs on the edge of the positive electrode material layer 112 and the burrs on the edge of the negative electrode material layer 122 are all parallel to the electrolyte sheet 130, and the burrs will not pierce the electrolyte sheet 130 to cause a short circuit between the positive electrode sheet 110 and the negative electrode sheet 120.

[0095] Exemplarily, the orthographic projection of the electrode material layer 11 in the XY plane is a rectangle, and the electrode block 20 formed after isostatic pressing is a cuboid, whose length direction is the X direction, width direction is the Y direction, and height direction is the Z direction. After cutting along the first preset direction, the length direction of the formed electrode material layer 11 is the X direction, the width direction is the Y direction, and the thickness direction is the Z direction.

[0096] In the above embodiment, the inner cavity of the mold is also a rectangular parallelepiped. For example, the length of the inner cavity of the mold is greater than or equal to 1000 mm and less than or equal to 2000 mm, the width of the inner cavity of the mold is greater than or equal to 500 mm and less than or equal to 1000 mm, and the height of the inner cavity of the mold is greater than or equal to 100 mm and less than or equal to 500 mm.

[0097] In an embodiment of the present application, an isostatic press is used to perform isostatic pressing on the material in the mold. The pressure applied during the isostatic pressing is greater than or equal to 300 MPa and less than or equal to 400 MPa, and the pressure application time is greater than or equal to 30 min and less than or equal to 60 min.

[0098] In the embodiment of the present application, a wire cutting device is used to cut the electrode block 20. The wire cutting device has high cutting accuracy and is convenient for controlling the thickness of the electrode material layer 11.

[0099] When the positive electrode material layer 112 is produced by the above-mentioned electrode sheet production method, the materials required for the positive electrode material layer 112 are added to the mixer according to the specified proportion. Specifically, the positive electrode active material powder, the solid electrolyte powder, and the conductive agent powder are added to the mixer according to the proportion of 65% to 89% by mass of the positive electrode active material, 5% to 35% by mass of the solid electrolyte, and 0.5% to 5% by mass of the conductive agent. The mixer stirs at a high speed to evenly mix the three materials of the positive electrode active material, the solid electrolyte, and the conductive agent. The mixed material is introduced into a mold and subjected to isostatic pressing by an isostatic press.

[0100] For the positive electrode material layer 112, the aforementioned first preset thickness is greater than or equal to 50 μm and less than or equal to 100 μm, preferably greater than or equal to 70 μm and less than or equal to 80 μm. The thickness tolerance range of the positive electrode material layer 112 is ±1 μm to 5 μm. If the thickness tolerance of the positive electrode material layer 112 is higher than ±1 μm, the thickness precision requirement of the positive electrode material layer 112 will be too high, production will be more difficult, and production costs will be excessively increased. If the thickness tolerance of the positive electrode material layer 112 is lower than ±5 μm, the bonding area between the positive electrode material layer 112 and the positive electrode current collector 111, and between the positive electrode material layer 112 and the electrolyte sheet 130 will be reduced, which will lead to problems such as increased internal resistance of the battery and cracking inside the battery cell 100.

[0101] When the negative electrode material layer 122 is produced by the above-mentioned electrode sheet production method, the materials required for the negative electrode material layer 122 are added to the mixer according to the specified proportion. Specifically, the negative electrode active material powder, the solid electrolyte powder, and the conductive agent powder are added to the mixer according to the proportion of 65% to 89% by mass of the negative electrode active material, 5% to 35% by mass of the solid electrolyte, and 0.5% to 5% by mass of the conductive agent. The mixer stirs at a high speed to evenly mix the three materials of the negative electrode active material, the solid electrolyte, and the conductive agent. The mixed material is introduced into a mold and subjected to isostatic pressing by an isostatic press.

[0102] For the negative electrode material layer 122, the aforementioned first preset thickness is greater than or equal to 10μm and less than or equal to 40μm, preferably greater than or equal to 20μm and less than or equal to 30μm. The thickness tolerance range of the negative electrode material layer 122 is ±1μm to 5μm. If the thickness tolerance of the negative electrode material layer 122 is higher than ±1μm, the thickness precision requirement of the negative electrode material layer 122 will be too high, production will be more difficult, and the production cost will be excessively increased. If the thickness tolerance of the negative electrode material layer 122 is lower than ±5μm, the bonding area between the negative electrode material layer 122 and the negative electrode current collector 121, and between the negative electrode material layer 122 and the electrolyte sheet 130 will be reduced, which will lead to problems such as increased internal resistance of the battery and cracking inside the battery cell 100.

[0103] Furthermore, the ratio of the thickness of the negative electrode material layer 122 to the thickness of the positive electrode material layer 112 is greater than or equal to 0.2 and less than or equal to 0.5, which can ensure that the energy of the negative electrode material layer 122 and the positive electrode material layer 112 match each other, ensure that the energy of the positive electrode material layer 112 is fully utilized as much as possible, and that neither the negative electrode material layer 122 nor the positive electrode material layer 112 will be wasted.

[0104] In the battery provided in the present application, the electrode sheet 10 of the battery cell 100 further includes an electrolyte sheet 130 .

[0105] Specifically, the material components of the electrolyte sheet 130 provided in the present application include a solid electrolyte, and the material components of the electrolyte sheet 130 do not include an adhesive. The ratio of the actual density of the electrolyte sheet 130 to the theoretical density of the electrolyte sheet 130 (i.e., the density) is greater than or equal to 95%, which can improve the conductivity of the electrolyte sheet 130, thereby improving the current transmission efficiency in the battery containing the electrolyte sheet 130, and improving the capacity and energy density of the battery.

[0106] In the electrolyte sheet 130 provided in the present application, since the material components of the electrolyte sheet 130 do not include an adhesive, there is almost no effect on the conductivity of the electrolyte sheet 130. Compared with the electrolyte sheet with an adhesive added, the conductivity of the electrolyte sheet 130 provided in the present application can be improved, thereby improving the current transmission efficiency in the battery.

[0107] In the prior art, since the electrolyte sheet 130 contains a material component of an adhesive, and the adhesive is an elastic polymer, it is difficult to achieve a high density when the electrolyte sheet 130 is compacted. Specifically, in the existing electrode sheet, the ratio of the actual density of the electrolyte sheet to the theoretical density of the electrolyte sheet is approximately 90%. Moreover, after the electrolyte sheet has been left to stand for a period of time, due to the strong elasticity of the adhesive, there is a problem of the electrolyte sheet rebounding, which causes the density of the electrolyte sheet of the electrode sheet to further drop to about 85%. However, since the electrolyte sheet 130 provided in the embodiment of the present application does not contain the material component of an adhesive, the influence of the adhesive on the density can be eliminated. After the electrolyte sheet 130 is compacted, the ratio of the actual density of the electrolyte sheet 130 to the theoretical density of the electrolyte sheet 130 can be greater than or equal to 95%, that is, the electrolyte sheet 130 has a higher density, thereby improving the capacity and energy density of the battery. Furthermore, since the electrolyte sheet 130 does not contain an adhesive, the problem of the electrolyte sheet 130 rebounding and causing a decrease in density will not occur, and the density of the electrolyte sheet 130 can be stably maintained at a state greater than or equal to 95%.

[0108] The solid electrolyte materials used to produce the electrolyte sheet 130 include sulfide electrolytes, halide electrolytes, oxide electrolytes, and polymer electrolytes. Sulfide electrolytes include LPSCl (lithium phosphorus sulfur chloride), LGPS (lithium germanium phosphorus sulfur solid electrolyte) and their derivatives; halide electrolytes include Li3YCl6, Li3InCl6 and their derivatives; oxide electrolytes include LLZO (lithium lanthanum zirconium oxide), LATP (lithium aluminum titanium phosphate), LLTO (lithium lanthanum titanate) and their derivatives. Any one of the above materials or a combination of at least two of them can be selected to produce the electrolyte sheet 130.

[0109] The battery production method provided in the embodiment of the present application also includes a production method of an electrolyte sheet, which is used to produce the electrolyte sheet 130 as described above. The production method of the electrolyte sheet can ensure that the density of the electrolyte sheet 130 meets the production requirements and improve the density uniformity of the electrolyte sheet 130. The production method of the electrolyte sheet includes:

[0110] R1, placing the materials required for manufacturing the electrolyte sheet 130 into a mold;

[0111] R2. Perform isostatic pressing on the material in the mold so that the ratio of the actual density of the material in the mold to the theoretical density of the material in the mold is greater than or equal to 95%.

[0112] In the production method of the electrolyte sheet provided in the present application, the materials required for producing the electrolyte sheet 130 are placed in a mold, and the materials in the mold are subjected to isostatic pressing treatment so that the materials in the mold are compacted tightly under pressure. No adhesive is added to the materials required for producing the electrolyte sheet 130. Only isostatic pressing treatment can ensure that the ratio of the actual density of the material in the mold to the theoretical density of the material in the mold can reach greater than or equal to 95%, thereby producing a high-density electrolyte sheet 130, which helps to improve the capacity and energy density of the battery. Moreover, isostatic pressing treatment can improve the density uniformity of the electrolyte sheet 130. When the battery is working, it can avoid problems such as uneven stress distribution and uneven temperature distribution on the electrolyte sheet 130, thereby preventing the occurrence of gaps between the electrolyte sheet 130 and the electrode sheet 10, which leads to battery capacity decline.

[0113] The thickness of the electrolyte sheet 130 to be produced is set to the second preset thickness. After the material in the mold is subjected to isostatic pressing, the electrolyte sheet 130 can be directly formed or the electrolyte sheet 130 can be formed by cutting the material after the isostatic pressing.

[0114] Specifically, in some embodiments, after the material in the mold is subjected to isostatic pressing, the material in the mold is formed into a sheet-shaped electrolyte sheet 130 under pressure, and the thickness of the electrolyte sheet 130 meets the second preset thickness. That is, one electrolyte sheet 130 is formed each time the isostatic pressing is performed.

[0115] In other embodiments, after the material in the mold is subjected to isostatic pressing, the material in the mold is formed into an electrolyte block 30 , and the thickness of the electrolyte block 30 is greater than the second preset thickness.

[0116] The production method of the electrolyte sheet further includes: after the electrolyte block 30 is formed, cutting the electrolyte block 30 along a second preset direction to divide the electrolyte block 30 into a plurality of electrolyte sheets 130, wherein the second preset direction is perpendicular to the thickness direction of the electrolyte sheet 130. Figure 7 , the electrolyte sheet 130 is parallel to the plane where the X direction and the Y direction are located (i.e., the XY plane), the thickness direction of the electrolyte sheet 130 is the Z direction, and the thickness direction of the electrolyte block 30 is also the Z direction. The X direction, the Y direction, and the Z direction are perpendicular to each other. The above-mentioned second preset direction is parallel to the plane where the X direction and the Y direction are located, and the electrolyte block 30 is cut multiple times along the second preset direction so that the electrolyte block 30 is divided into several layers of electrolyte sheets 130, and the thickness of each electrolyte sheet 130 meets the second preset thickness.

[0117] The solution of first isostatically pressing the material in the mold to form the electrolyte block 30 and then cutting the electrolyte block 30 along the second preset direction can improve the production efficiency of the electrolyte sheet 130, and facilitate the control of the thickness of the electrolyte sheet 130 to ensure the thickness uniformity of the electrolyte sheet 130.

[0118] Exemplarily, the orthographic projection of the electrolyte sheet 130 in the XY plane is a rectangle, and the electrolyte block 30 formed after isostatic pressing is a cuboid, whose length direction is the X direction, width direction is the Y direction, and height direction is the Z direction. After cutting along the second preset direction, the length direction of the formed electrolyte sheet 130 is the X direction, the width direction is the Y direction, and the thickness direction is the Z direction.

[0119] In the above embodiment of producing the electrolyte sheet 130, the inner cavity of the mold is also a rectangular parallelepiped. For example, the length dimension of the inner cavity of the mold is greater than or equal to 1000 mm and less than or equal to 2000 mm, the width dimension of the inner cavity of the mold is greater than or equal to 500 mm and less than or equal to 1000 mm, and the height dimension of the inner cavity of the mold is greater than or equal to 100 mm and less than or equal to 500 mm.

[0120] In the embodiment of the present application, when producing the electrolyte sheet 130, an isostatic press is used to perform isostatic pressing on the material in the mold. The pressure applied during the isostatic pressing is greater than or equal to 300 MPa and less than or equal to 400 MPa, and the pressure application time is greater than or equal to 30 minutes and less than or equal to 60 minutes.

[0121] In the embodiment of the present application, a wire cutting device is used to cut the electrolyte block 30. The wire cutting device has high cutting accuracy and is convenient for controlling the thickness of the electrolyte sheet 130.

[0122] When the electrolyte sheet 130 is produced by the above-mentioned production method of the electrolyte sheet, the solid electrolyte powder is poured into a mold and subjected to isostatic pressing by an isostatic press.

[0123] For the electrolyte sheet 130 , the second preset thickness is greater than or equal to 0.01 mm and less than or equal to 0.02 mm, and is preferably 0.015 mm.

[0124] like Figure 8 and Fig. 9 As shown, the present application also provides a battery cell 100, the conductivity of which can be improved, thereby improving the transmission efficiency of current in the battery, and increasing the capacity and energy density of the battery. The battery cell 100 includes the electrode sheet 10 provided in any of the above embodiments and / or the electrolyte sheet 130 provided in any of the above embodiments, and the electrode sheet 10 and the electrolyte sheet 130 are stacked.

[0125] Specifically, the battery cell 100 includes a positive electrode sheet 110 and a negative electrode sheet 120, and an electrolyte sheet 130 is located between the positive electrode sheet 110 and the negative electrode sheet 120. The material components of the positive electrode material layer 112 of the positive electrode sheet 110 do not include a binder, and the ratio of the actual density of the positive electrode material layer 112 to the theoretical density of the positive electrode material layer 112 is greater than or equal to 95%; and / or, the material components of the negative electrode material layer 122 of the negative electrode sheet 120 do not include a binder, and the ratio of the actual density of the negative electrode material layer 122 to the theoretical density of the negative electrode material layer 122 is greater than or equal to 95%; and / or, the material components of the electrolyte sheet 130 do not include a binder, and the ratio of the actual density of the electrolyte sheet 130 to the theoretical density of the electrolyte sheet 130 is greater than or equal to 95%.

[0126] like Figure 8 As shown, in some embodiments, the battery cell 100 includes a negative electrode sheet 120, an electrolyte sheet 130, a positive electrode sheet 110, an electrolyte sheet 130, and a negative electrode sheet 120 stacked in sequence, wherein the positive electrode sheet 110 includes a positive electrode collector 111 and a positive electrode material layer 112 disposed on both sides of the positive electrode collector 111, and the negative electrode sheet 120 includes a negative electrode collector 121 and a negative electrode material layer 122 disposed on one side of the negative electrode collector 121. The electrolyte sheet 130 is disposed on the side of the positive electrode material layer 112 facing away from the positive electrode collector 111, and the electrolyte sheet 130 is in contact with the negative electrode material layer 122. Further, an insulating glue layer 14 is disposed on the side of the negative electrode collector 121 facing away from the negative electrode material layer 122 to insulate the battery cell 100 from adjacent battery cells 100.

[0127] In the above embodiment, the negative electrode sheet 120, the electrolyte sheet 130, the positive electrode sheet 110, the electrolyte sheet 130 and the negative electrode sheet 120 are stacked in order, and the stacked structure is subjected to hot pressing treatment to make the negative electrode sheet 120, the electrolyte sheet 130 and the positive electrode sheet 110 closely fit each other. Specifically, the temperature during the hot pressing treatment is 60°C to 200°C, preferably 140°C to 170°C; the pressure during the hot pressing treatment is 5MPa to 50MPa, preferably 20MPa to 30MPa; the duration of the hot pressing treatment is 30s to 120s, preferably 60s to 80s.

[0128] like Fig. 9As shown, in some embodiments, the battery cell 100 includes a positive electrode sheet 110, an electrolyte sheet 130, a negative electrode sheet 120, an electrolyte sheet 130 and a positive electrode sheet 110 stacked in sequence, wherein the negative electrode sheet 120 includes a negative electrode collector 121 and a negative electrode material layer 122 disposed on both sides of the negative electrode collector 121, and the positive electrode sheet 110 includes a positive electrode collector 111 and a positive electrode material layer 112 disposed on one side of the positive electrode collector 111. The electrolyte sheet 130 is disposed on the side of the negative electrode material layer 122 facing away from the negative electrode collector 121, and the electrolyte sheet 130 is in contact with the positive electrode material layer 112 of the positive electrode sheet 110. Further, an insulating glue layer 14 is disposed on the side of the positive electrode collector 111 facing away from the positive electrode material layer 112 to insulate the battery cell 100 from adjacent battery cells 100.

[0129] In the above embodiment, the positive electrode sheet 110, the electrolyte sheet 130, the negative electrode sheet 120, the electrolyte sheet 130 and the positive electrode sheet 110 are stacked in sequence, and the stacked structure is subjected to hot pressing treatment to make the negative electrode sheet 120, the electrolyte sheet 130 and the positive electrode sheet 110 closely fit each other. Specifically, the temperature during the hot pressing treatment is 60°C to 200°C, preferably 140°C to 170°C; the pressure during the hot pressing treatment is 5MPa to 50MPa, preferably 20MPa to 30MPa; the duration of the hot pressing treatment is 30s to 120s, preferably 60s to 80s.

[0130] like Fig.10 As shown, the battery provided in the embodiment of the present application includes a packaging structure 200 and at least one battery cell 100 as described above, and the battery cell 100 is located in the packaging structure 200. The battery with the above battery cell 100 can improve the transmission efficiency of the current in the battery, and enhance the capacity and energy density of the battery.

[0131] Exemplarily, a plurality of battery cells 100 are provided along the thickness direction, such as 2 to 50. In two adjacent battery cells 100, the positive electrode tab 1110 of one and the negative electrode tab 1210 of the other are conductively connected through a connecting sheet 300. A heat conducting layer 400 is provided between two adjacent battery cells 100 to facilitate achieving temperature consistency of multiple battery cells 100 inside the battery.

[0132] See also Fig.10 The positive electrode tab 1110 of the top battery cell 100 is electrically connected to the battery positive electrode tab 500, and the negative electrode tab 1210 of the bottom battery cell 100 is electrically connected to the battery negative electrode tab 600. Both the battery positive electrode tab 500 and the battery negative electrode tab 600 are partially disposed outside the packaging structure 200.

[0133] Further, the packaging structure 200 may include an aluminum-plastic film structure, wherein the aluminum-plastic film structure includes an upper aluminum-plastic film and a lower aluminum-plastic film arranged opposite to each other, the battery cell 100 is placed between the upper aluminum-plastic film and the lower aluminum-plastic film, and the edge area of ​​the upper aluminum-plastic film and the edge area of ​​the lower aluminum-plastic film are stacked and bonded together so that the upper aluminum-plastic film and the lower aluminum-plastic film seal and wrap the battery cell 100.

[0134] The positive electrode sheet 110 , the negative electrode sheet 120 , and the electrolyte sheet 130 provided in the present application are described in detail below by way of specific embodiments.

[0135] Specifically, the advantages of the positive electrode plate 110 provided in the present application are described below with reference to Examples 1 to 6 and Comparative Example 1.

[0136] Example 1

[0137] This embodiment provides a battery, wherein the battery cell 100 includes a positive electrode plate 110, wherein the material components of the positive electrode material layer 112 of the positive electrode plate 110 do not include an adhesive, and the ratio of the actual density of the positive electrode material layer 112 to the theoretical density of the positive electrode material layer 112 is greater than or equal to 95%.

[0138] The mass proportions of the material components in the positive electrode material layer 112 are: the mass proportion of the positive electrode active material is 85%, the mass proportion of the solid electrolyte is 10%, and the mass proportion of the conductive agent is 5%. The pressure of the isostatic pressing treatment when producing the positive electrode material layer 112 is 400 MPa, and the pressure maintenance time is 60 minutes.

[0139] Example 2

[0140] This embodiment provides a battery, wherein a battery cell 100 of the battery includes a positive electrode sheet 110, and the difference between the positive electrode sheet 110 and the embodiment 1 is that:

[0141] The mass proportions of the various material components in the positive electrode material layer 112 are as follows: the mass proportion of the positive electrode active material is 85%, the mass proportion of the solid electrolyte is 12%, and the mass proportion of the conductive agent is 3%.

[0142] Example 3

[0143] This embodiment provides a battery, wherein a battery cell 100 of the battery includes a positive electrode sheet 110, and the difference between the positive electrode sheet 110 and the embodiment 1 is that:

[0144] The mass proportions of the various material components in the positive electrode material layer 112 are as follows: the mass proportion of the positive electrode active material is 85%, the mass proportion of the solid electrolyte is 14%, and the mass proportion of the conductive agent is 1%.

[0145] Example 4

[0146] This embodiment provides a battery, wherein a battery cell 100 includes a positive electrode sheet 110, which is different from the embodiment 1 in that:

[0147] When producing the positive electrode material layer 112, the pressure of the isostatic pressing treatment is 400 MPa, and the pressure maintenance time is 40 minutes.

[0148] Example 5

[0149] This embodiment provides a battery, wherein a battery cell 100 includes a positive electrode sheet 110, which is different from the embodiment 1 in that:

[0150] When producing the positive electrode material layer 112, the pressure of the isostatic pressing treatment is 300 MPa, and the pressure maintenance time is 40 minutes.

[0151] Example 6

[0152] This embodiment provides a battery, wherein a battery cell 100 includes a positive electrode sheet 110, which is different from the embodiment 1 in that:

[0153] When producing the positive electrode material layer 112, the pressure of the isostatic pressing treatment is 400 MPa, and the pressure maintenance time is 10 minutes.

[0154] Comparative Example 1

[0155] This comparative example provides a battery, wherein the battery cell 100 includes a positive electrode sheet 110, which is different from the embodiment 1 in that:

[0156] The mass proportions of the material components in the positive electrode material layer 112 are: the mass proportion of the positive electrode active material is 75%, the mass proportion of the solid electrolyte is 18.5%, the mass proportion of the conductive agent is 5%, and the mass proportion of the adhesive is 1.5%.

[0157] The resistance test of the positive electrode material layer 112 provided in the above-mentioned embodiments 1 to 6 and comparative example 1 is performed, and the resistance of the positive electrode material layer 112 obtained is as follows:

[0158]

[0159] It can be seen from the above table that, compared with Comparative Example 1, the positive electrode material layer 112 in Examples 1 to 6 does not include a binder in the material components, and the resistance is smaller than that of the positive electrode material layer 112 provided in Comparative Example 1. The smaller the resistance, the higher the conductivity. Therefore, the conductivity of the positive electrode material layer 112 in Examples 1 to 6 is higher than the conductivity of the positive electrode material layer 112 provided in Comparative Example 1. Moreover, the higher the mass proportion of the conductive agent, the smaller the resistance of the positive electrode material layer 112, and the higher the conductivity; the higher the pressure during the isostatic pressing treatment, the higher the conductivity of the positive electrode material layer 112; the longer the isostatic pressing treatment time, the higher the conductivity of the positive electrode material layer 112.

[0160] Specifically, the advantages of the negative electrode plate 120 provided in the present application are described below with reference to Examples 7 to 12 and Comparative Example 2.

[0161] Example 7

[0162] This embodiment provides a battery, wherein the battery cell 100 includes a negative electrode plate 120, wherein the negative electrode material layer 122 of the negative electrode plate 120 does not include a binder, and the ratio of the actual density of the negative electrode material layer 122 to the theoretical density of the negative electrode material layer 122 is greater than or equal to 95%.

[0163] The mass proportions of the material components in the negative electrode material layer 122 are: the mass proportion of the negative electrode active material is 85%, the mass proportion of the solid electrolyte is 10%, and the mass proportion of the conductive agent is 5%. The pressure of the isostatic pressing treatment when producing the negative electrode material layer 122 is 400 MPa, and the pressure maintenance time is 60 minutes.

[0164] Example 8

[0165] This embodiment provides a battery, wherein the battery cell 100 includes a negative electrode plate 120, which is different from the embodiment 7 in that:

[0166] The mass proportions of the various material components in the negative electrode material layer 122 are as follows: the mass proportion of the negative electrode active material is 85%, the mass proportion of the solid electrolyte is 12%, and the mass proportion of the conductive agent is 3%.

[0167] Example 9

[0168] This embodiment provides a battery, wherein the battery cell 100 includes a negative electrode plate 120, which is different from the embodiment 7 in that:

[0169] The mass proportions of the various material components in the negative electrode material layer 122 are as follows: the mass proportion of the negative electrode active material is 85%, the mass proportion of the solid electrolyte is 14%, and the mass proportion of the conductive agent is 1%.

[0170] Example 10

[0171] This embodiment provides a battery, wherein the battery cell 100 includes a negative electrode plate 120, which is different from the embodiment 7 in that:

[0172] The pressure of the isostatic pressing treatment when producing the negative electrode material layer 122 is 400 MPa, and the pressure maintenance time is 40 minutes.

[0173] Embodiment 11

[0174] This embodiment provides a battery, wherein the battery cell 100 includes a negative electrode plate 120, which is different from the embodiment 7 in that:

[0175] The pressure of the isostatic pressing treatment when producing the negative electrode material layer 122 is 300 MPa, and the pressure maintenance time is 40 minutes.

[0176] Example 12

[0177] This embodiment provides a battery, wherein the battery cell 100 includes a negative electrode plate 120, which is different from the embodiment 7 in that:

[0178] The pressure of the isostatic pressing treatment when producing the negative electrode material layer 122 is 400 MPa, and the pressure maintenance time is 10 minutes.

[0179] Comparative Example 2

[0180] This comparative example provides a battery, wherein the battery cell 100 includes a negative electrode plate 120, which is different from Example 7 in that:

[0181] The mass proportions of the material components in the negative electrode material layer 122 are: the mass proportion of the negative electrode active material is 75%, the mass proportion of the solid electrolyte is 18.5%, the mass proportion of the conductive agent is 5%, and the mass proportion of the binder is 1.5%.

[0182] The resistance test of the negative electrode material layer 122 provided in the above-mentioned embodiments 7 to 12 and comparative example 2 is performed, and the resistance of the negative electrode material layer 122 obtained is as follows:

[0183]

[0184] It can be seen from the above table that, compared with Comparative Example 2, the negative electrode material layer 122 in Examples 7 to 12 does not include a binder in the material components, and the resistance is smaller than that of the negative electrode material layer 122 provided in Comparative Example 1. The smaller the resistance, the higher the conductivity. Therefore, the conductivity of the negative electrode material layer 122 in Examples 7 to 12 is higher than that of the negative electrode material layer 122 provided in Comparative Example 2. Moreover, the higher the mass proportion of the conductive agent, the smaller the resistance of the negative electrode material layer 122, and the higher the conductivity; the higher the pressure during the isostatic pressing treatment, the higher the conductivity of the negative electrode material layer 122; the longer the isostatic pressing treatment time, the higher the conductivity of the negative electrode material layer 122.

[0185] Specifically, the advantages of the electrolyte sheet 130 provided in the present application are described below with reference to Examples 13 to 15 and Comparative Examples 3 to 5.

[0186] Example 13

[0187] This embodiment provides an electrolyte sheet 130, wherein the material components of the electrolyte sheet 130 do not include an adhesive, and the ratio of the actual density of the electrolyte sheet 130 to the theoretical density of the electrolyte sheet 130 is greater than or equal to 95%. When producing the electrolyte sheet 130, the pressure of the isostatic pressing treatment is 400 MPa, and the pressure maintenance time is 40 minutes.

[0188] Embodiment 14

[0189] This embodiment provides an electrolyte sheet 130, which is different from the embodiment 13 in that:

[0190] When producing the electrolyte sheet 130, the pressure of the isostatic pressing treatment is 300 MPa, and the pressure maintenance time is 40 minutes.

[0191] Embodiment 15

[0192] This embodiment provides an electrolyte sheet 130, which is different from the embodiment 13 in that:

[0193] When producing the electrolyte sheet 130, the pressure of the isostatic pressing treatment is 400 MPa, and the pressure maintenance time is 10 minutes.

[0194] Comparative Example 3

[0195] This embodiment provides an electrolyte sheet 130, which is different from the embodiment 13 in that:

[0196] The material components of the electrolyte sheet 130 include a solid electrolyte and an adhesive, wherein the solid electrolyte accounts for 97% by mass and the adhesive accounts for 3% by mass.

[0197] Comparative Example 4

[0198] This embodiment provides an electrolyte sheet 130, which is different from the embodiment 13 in that:

[0199] The material components of the electrolyte sheet 130 include a solid electrolyte and an adhesive, wherein the solid electrolyte accounts for 98% by mass and the adhesive accounts for 2% by mass.

[0200] Comparative Example 5

[0201] This embodiment provides an electrolyte sheet 130, which is different from the embodiment 13 in that:

[0202] The material components of the electrolyte sheet 130 include a solid electrolyte and an adhesive, wherein the solid electrolyte accounts for 99% by mass and the adhesive accounts for 1% by mass.

[0203] Since the conductivity of the electrolyte sheet 130 can be directly measured, the conductivity test of the electrolyte sheet 130 provided in Examples 13 to 15 and Comparative Examples 3 to 5 is performed, and the conductivity of the electrolyte sheet 130 obtained is as shown in the following table:

[0204]

[0205] It can be seen from the above table that, compared with Comparative Examples 3 to 5, the electrolyte sheet 130 in Examples 13 to 15 has a higher conductivity because the material components do not include an adhesive. Moreover, when producing the electrolyte sheet 130, the higher the pressure during the isostatic pressing treatment, the higher the conductivity of the electrolyte sheet 130; the longer the isostatic pressing treatment time, the higher the conductivity of the electrolyte sheet 130. In Comparative Examples 3 to 5, even if the mass proportion of the adhesive in the electrolyte sheet 130 is reduced to 1%, its conductivity is still significantly lower than that of the electrolyte sheet 130 without an adhesive.

[0206] Obviously, the above embodiments of the present application are merely examples for clearly illustrating the present application, and are not intended to limit the implementation methods of the present application. For those of ordinary skill in the art, various obvious changes, readjustments, and substitutions can be made without departing from the protection scope of the present application. It is not necessary and impossible to list all implementation methods exhaustively here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present application shall be included in the protection scope of the claims of the present application.

Claims

1. A battery, characterized in that The invention comprises a battery cell (100), wherein the battery cell (100) comprises an electrode sheet (10), wherein the electrode sheet (10) comprises an electrode material layer (11), wherein the material components of the electrode material layer (11) do not include an adhesive, and the material components of the electrode material layer (11) include an electrode active material and a conductive agent.

2. The battery according to claim 1, characterized in that The material components of the electrode material layer (11) also include a solid electrolyte.

3. The battery according to claim 2, characterized in that The mass proportion of the electrode active material in the electrode material layer (11) is greater than or equal to 65% and less than or equal to 89%, and the mass proportion of the electrode active material is the percentage of the mass of the electrode active material in the electrode material layer (11) to the total mass of the electrode material layer (11); And / or, the mass proportion of the solid electrolyte in the electrode material layer (11) is greater than or equal to 5% and less than or equal to 35%, and the mass proportion of the solid electrolyte is the percentage of the mass of the solid electrolyte in the electrode material layer (11) to the total mass of the electrode material layer (11); And / or, the mass proportion of the conductive agent in the electrode material layer (11) is greater than or equal to 0.5% and less than or equal to 5%, and the mass proportion of the conductive agent is the percentage of the mass of the conductive agent in the electrode material layer (11) to the total mass of the electrode material layer (11).

4. The battery according to any one of claims 1 to 3, characterized in that: The ratio of the actual density of the electrode material layer (11) to the theoretical density of the electrode material layer (11) is greater than or equal to 95%.

5. The battery according to any one of claims 1 to 3, characterized in that: The electrode sheet (10) further comprises a current collector (12), and the electrode material layer (11) is stacked on at least one side of the current collector (12).

6. The battery according to claim 5, characterized in that The electrode sheet (10) further comprises a conductive adhesive layer (13), and the electrode material layer (11) and the current collector (12) are bonded and connected via the conductive adhesive layer (13).

7. The battery according to any one of claims 1 to 3, characterized in that: The electrode sheet (10) further comprises an electrolyte sheet (130), wherein the material components of the electrolyte sheet (130) include a solid electrolyte and do not include an adhesive.

8. The battery according to claim 7, characterized in that The ratio of the actual density of the electrolyte sheet (130) to the theoretical density of the electrolyte sheet (130) is greater than or equal to 95%.

9. A battery production method, characterized in that: Used to produce a battery as claimed in any one of claims 1 to 8, wherein the battery production method includes a method for producing an electrode sheet, and the method for producing an electrode sheet includes: Putting materials required for manufacturing the electrode material layer (11) into a mold; The material in the mold is subjected to isostatic pressing so that the ratio of the actual density of the material in the mold to the theoretical density of the material in the mold is greater than or equal to 95%.

10. The battery production method according to claim 9, characterized in that: The thickness of the electrode material layer (11) to be produced is a first preset thickness; After isostatic pressing the material in the mold, the material in the mold is formed into an electrode material layer (11) having a thickness satisfying a first preset thickness; or, After isostatic pressing the material in the mold, the material in the mold is formed into an electrode block (20), and the thickness of the electrode block (20) is greater than a first preset thickness; The method for producing the electrode sheet further comprises: cutting the electrode block (20) along a first preset direction so that the electrode block (20) is divided into a plurality of electrode material layers (11), wherein the first preset direction is perpendicular to the thickness direction of the electrode material layer (11).

11. The battery production method according to claim 9, characterized in that: The battery production method also includes a method for producing an electrolyte sheet, and the method for producing an electrolyte sheet includes: Putting materials required for manufacturing the electrolyte sheet (130) into a mold; The material in the mold is subjected to isostatic pressing so that the ratio of the actual density of the material in the mold to the theoretical density of the material in the mold is greater than or equal to 95%.

12. The battery production method according to claim 11, characterized in that: The thickness of the electrolyte sheet (130) to be produced is a second preset thickness; After isostatic pressing the material in the mold, the material in the mold is formed into an electrolyte sheet (130) having a thickness satisfying a second preset thickness; or, After isostatic pressing is performed on the material in the mold, the material in the mold is formed into an electrolyte block (30), and the thickness of the electrolyte block (30) is greater than the second preset thickness; the production method of the electrolyte sheet further comprises: cutting the electrolyte block (30) along a second preset direction to divide the electrolyte block (30) into a plurality of electrolyte sheets (130), and the second preset direction is perpendicular to the thickness direction of the electrolyte sheet (130).

Citation Information

Patent Citations

  • Batteries including solid and liquid electrolyte

    CN107180994A

  • A device and a method for processing a battery pole piece

    CN109244372A

  • Electrode pole piece, preparation method thereof and solid-state battery

    CN110581253A

  • Composite positive plate, preparation method and solid-liquid mixed lithium storage battery

    CN110931845A

  • Negative electrode material, preparation method and application thereof

    CN111564607A